INTEGRATION OF SOCIAL PROCESSES IN THE NEIGHBORHOOD - Tishabayeva Lola Arifovna (American Journals Publishing, 2023)
The article examines the topical problems of reforming the system of mahallas in Uzbekistan, the peculiarities of organizing the activities of multinational, religious communities and democratic factors in the years of independence, It is narrated on the content of the Mahallabay Working System.
Keywords: Ministry of Mahalla and Family Support, Appeal to Oliy Majlis